Potential of Trichoderma asperellum in Suppressing the Growth of Several Fungal Pathogens in Rice In Vitro - Arianti, Selvia; Nurbailis; Darnetty (Akta Agrosia, 2025)
Rice (Oryza sativa L.) is an important food crop with Helminthosporium oryzae B. de Haan, Curvularia sp., and Rhizoctonia solani as three major associated pathogenic fungi. In controlling these pathogens, the use of antagonistic fungus, such as Trichoderma asperellum, is still considered the most effective and environmentally friendly. The study aimed to determine the potential of T. asperellum in suppressing several pathogenic fungi that cause disease in rice plants in vitro. The study used a completely randomized design (CRD) with 4 treatments and 10 replicates. The treatments were several pathogens that cause disease in rice plants with antagonistic fungi T. asperellum to inhibit several pathogens in rice plants, namely R. solani, Curvularia sp., H. oryzae., and untreated control. Testing the antagonistic power of T. asperellum against several pathogenic fungi was carried out by double culture method and culture vapor method. Observations made included the percentage of inhibition, invasion rate, colony area, changes in morphological characters, the number of conidia and the number of germinated conidia. The results showed that T. asperellum has the potential to suppress the growth of several pathogenic fungi studied in vitro. In the double culture method, T. asperellum suppressed the growth of R. solani fungus with the highest inhibition percentage of 68.40%, whereas in the vapor culture method, T. asperellum suppressed the growth of Curvularia sp. fungus with the highest effectiveness of 62.04%. Keywords: biological control, Curvularia sp., Helminthosporium oryzae, Rhizoctonia solani